Helicobacter pylori and Its Antibiotic Heteroresistance: A Neglected Issue in Published Guidelines - Rizvanov, Albert A.; Haertlé, Thomas; Bogomolnaya, Lydia; Talebi Bezmin Abadi, Amin (Frontiers in Microbiology, 2019)
‘‘Heteroresistance’’ is a widely applied term that characterizes most of the multidrug-resistant microorganisms. In microbiological practice, the word ‘‘heteroresistance’’ indicates diverse responses to specific antibiotics by bacterial subpopulations in the same patient. These resistant subpopulations of heteroresistant strains do not respond to antibiotic therapy in vitro or in vivo. Presently, there is no standard protocol available for the treatment of infections caused by heteroresistant Helicobacter pylori in clinical settings, at least according to recent guidelines. Thus, there is a definite need to open a new discussion on how to recognize, how to screen and how to eliminate those problematic strains in clinical and environmental samples. Since there is great interest in developing new strategies to improve the eradication rate of anti-H. pylori treatments, the presence of heteroresistant strains/clones among clinical isolates of the bacteria should be taken into account. Indeed, increased knowledge of gastroenterologists about the existence of heteroresistance phenomena is highly required. Moreover, the accurate breakpoints should be examined/determined in order to have a solid statement of heteroresistance among the H. pylori isolates. The primary definition of heteroresistance was about coexistence of both resistant and susceptible isolates at the similar gastric microniche at once, while we think that it can be happened subsequently as well. The new guidelines should include a personalized aspect in the standard protocol to select the precise effective antibiotic therapy for infected patients and also address the problems of regional antibiotic susceptibility profiles.